Des droits à reconnaître: les lesbiennes face à la discrimination - Bonneau, Micheline; Demczuk, Irène (Collection Les Entêtées, 1998)
Regroupant recherches et analyses, témoignages et récits personnels, ce livre rend compte de la discrimination vécue par les lesbiennes. Malgré que le Québec ait adopté une Charte des droits de la personne qui interdit toute discrimination basée sur l'orientation sexuelle, il faut reconnaître que l'adoption de ce principe d'équité n'a pas fait disparaître toute trace d'hétérosexisme dans la société. Les lesbiennes ne bénéficient pas encore d'une égalité juridique formelle, encore moins réelle.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; lesbophobie; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; shm4000; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

Lessons from the intersexed - Kessler, Suzanne J. (Rutgers University Press, 1998)
From the moment intersexuality-the condition of having physical gender markers (genitals, gonads, or chromosomes) that are neither clearly female nor male-is suspected and diagnosed, social institutions are mobilized in order to maintain the two seemingly objective sexual categories. Infants' bodies are altered, and what was "ambiguous" is made "normal." Kessler's interviews with pediatric surgeons and endocrinologists reveal how the intersex condition is normalized for parents and she argues that the way in which intersexuality is managed by the medical and psychological professions displays our culture's beliefs about gender and genitals. Parents of intersexed children are rarely heard from, but in this book they provide another perspective on reasons for genital surgeries and the quality of medical and psychological management. Although physicians educate parents about how to think about their children's condition, Kessler learned from parents of intersexed children that some parents are able to accept atypical genitals. Based on analysis of the medical literature and interview with adults who had received treatment as interesexed children, Kessler proposes new approaches for physicians to use in talking with parents and children. She also evaluates the appearance of a politicized vanguard, many of who are promoting an intersexual identity, who seek to alter the way physicians respond to intersexuality. Kessler explores the possibilities and implications of suspending a commitment to two "natural" genders and addresses gender destabilization issues arising from intersexuality. She thus compels readers to re-think the meaning of gender, genitals, and sexuality.
Keywords: LGBTQIA2+; approches et analyses; capacitisme; care; corps; cours; discipline; ethnographie; intersexuation; premier cycle; psychologie; santé; sciences humaines; soc2014; système de genre; systèmes d'oppressions; thématiques; violences; violences médicales

Quand la violence parle du sexe : analyse du discours thérapeutique pour hommes violents - Letarte, Lise (Université du Québec à Montréal, 1998)
Keywords: IREF; amériques; discipline; hommes* violents; mémoires/thèses; québec; régions géographiques; sciences humaines; sexologie; thématiques; violences; violences contre les femmes*

Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences

The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation in the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; atlanta; discipline; ethnographie; genre; harcèlement sexuel; masculinisme; montréal; mémoires/thèses; nouvelle-orléans; patriarcat; philosophie; périodes historiques; régions géographiques; résistance; san francisco; sciences humaines; systèmes d'oppressions; thématiques; violences

Science, conscience et action : vingt-cinq ans de recherche féministe au Québec - Dagenais, Huguette (Les éditions du remue-ménage, 1996)
Après un quart de siècle de néoféminisme, on connaît encore mal la recherche féministe et l’ampleur du travail accompli par ces chercheuses. Les auteures examinent ici les travaux qui ont porté sur la famille, la conciliation travail-famille et sur l’emploi, ceux qui ont documenté des aspects particuliers de la santé des femmes et de la violence conjugale ainsi que les nombreuses études produites dans le domaine de l’éducation. Elles mettent également en lumière les changements et les résistances révélés par les recherches dans le champ religieux, le champ politique, celui du droit de même que dans le domaine des communications. Ce faisant, elles rendent manifestes les caractéristiques de la recherche féministe québécoise, notamment les liens établis par les chercheuses entre théorie et pratique, recherche et action. Des textes de Pierrette Bouchard, Anita Caron, Renée Cloutier, Christine Corbeil, Huguette Dagenais, René B.-Dandurand, Francine Descarries, Louise Guyon, Thérèse Hamel, Geneviève Martin, Karen Messing, Josée Néron, Ann Robinson, Armande Saint-Jean, Diane-Gabrielle Tremblay et Manon Tremblay.
Keywords: 1900-1999; amériques; conciliation famille-travail; cours; discipline; droit; famille; fem1000; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; santé; science des religions; science politique; science politique et droit; sciences humaines; thématiques; théologie; violences; violences contre les femmes*

Taboo: Sex, identity, and erotic subjectivity in anthropological fieldwork - Kulick, Don; Willson, Margaret (Routledge, 1995)
Taboo looks at the ethnographer and sexuality in anthropological fieldwork and considers the many roles that sexuality plays in the anthropological production of knowledge and texts. How does the sexual identity that anthropologists have in their "home" society affect the kind of sexuality they are allowed to express in other cultures? How is the anthropologists' sexuality perceived by the people with whom he or she does research? How common is sexual violence and intimidation in the field and why is its existence virtually unmentioned in anthropology? These are but a few of the questions to be confronted, exploring from differing perspectives the depth of the influence this tabooed topic has on the entire practice and production of anthropology. A long-overdue text for all students and lecturers of anthropology, many post-fieldwork readers will find a resonance of issues they have previously faced (or tried to avoid) and those who are still to undertake fieldwork will find articles that refer to other kinds of personal and professional experience as well as providing invaluable preparations for coping in the field.other kinds of personal and professional experience as well as providing invaluable preparations for coping in the field.other kinds of personal and professional experience as well as providing invaluable preparations for coping in the field.other kinds of personal and professional experience as well as providing invaluable preparations for coping in the field.
Keywords: anthropologie; discipline; identités; ressource en ligne; sciences humaines; sexualité; thématiques; violences; violences sexuelles

Only words - MacKinnon, Catharine A. (Harvard University Press, 1993)
When is rape not a crime? When it's pornography--or so First Amendment law seems to say: in film, a rape becomes "free speech." Pornography, Catharine MacKinnon contends, is neither speech nor free. Pornography, racial and sexual harassment, and hate speech are acts of intimidation, subordination, terrorism, and discrimination, and should be legally treated as such. Only Words is a powerful indictment of a legal system at odds with itself, its First Amendment promoting the very inequalities its Fourteenth Amendment is supposed to end. In the bold and compelling style that has made her one of our most provocative legal critics, MacKinnon depicts a society caught in a vicious hypocrisy. Words that offer bribes or fix prices or segregate facilities are treated by law as acts, but words and pictures that victimize and target on the basis of race and sex are not. Pornography--an act of sexual domination reproduced in the viewing--is protected by law in the name of "the free and open exchange of ideas." But the proper concern of law, MacKinnon says, is not what speech says, but what it does. What the "speech" of pornography and of racial and sexual harassment and hate propaganda does is promote and enact the power of one social group over another. Cutting with surgical deftness through cases of harassment in the workplace and on college campuses, through First Amendment cases involving Nazis, Klansmen, and pornographers, MacKinnon shows that as long as discriminatory practices are protected as free speech, equality will be only a word.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sciences sociales; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques; violences; états-unis; études de genres

The interpretation of the flesh: Freud and femininity - Brennan, Teresa (Routledge, 1992)
The 'riddle of femininity', like Freud's reference to women's sexuality as a 'dark continent', has been treated as a romantic aside or a sexist evasion rather than as a problem to be solved. In this first comprehensive study, Teresa Brennan suggests that by placing these ideas in the context of Freud's work as a whole, we will begin to understand why femininity was such a riddle for Freud. Brennan argues that by turning to Freud's work and his concrete questions about femininity, a psychical state which occurs in men and women alike, the problem is clearly a soluble one, provided that Freud's concern with energy is taken into account. The real riddle of femininity is as much a problem for thinking about physicality as a problem for the subject who suffers from what Freud described as 'femininity's negative effects on curiosity, intelligence and activity.
Keywords: 1900-1999; cours; discipline; fem1000; féminité; histoire; premier cycle; psychanalyse; psychologie; périodes historiques; ressource en ligne; sciences; sciences humaines; thématiques; violences

Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (Gender & American culture, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

Les femmes autochtones et la justice pénale - Jaccoud, Mylène (Criminologie, 1992)
The interest in understanding and analyzing the situation of native women within the penal process is recent and seems to be limited by the inordinate attention paid by researchers to the overrepresentation of native women. This article is an account of the findings and analyses made to date in this recent sector of research. It presents an inventory of the principal data concerning the confrontation of native women with the penal process. It proposes a synthesis of the principal analyses of the problems of native women with the system of justice by presenting a critical analysis of the socio-structural model of LaPrairie.
Keywords: amériques; approches et analyses; canada; cours; criminologie; discipline; droit; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; pol4105; premier cycle; racisme; régions géographiques; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Emprise et violence maternelles: étude d'anthropologie psychanalytique - Couchard, Françoise (Psychismes, 0335-492X, 1991)
A partir d'exemples culturels et de cas empruntés à la clinique quotidienne, cet ouvrage montre les effets psychologiques d'une réduction de la personnalité féminine à sa seule fonction de reproduction : en particulier les comportements d'agression de la mère vis-à-vis de sa ou de ses filles.
Keywords: 1900-1999; anthropologie; cours; discipline; europe; fem1000; figure de la mère; france; maternité; premier cycle; psychanalyse; périodes historiques; régions géographiques; sciences humaines; thématiques; violences; violences familiales

Feminist Debates about Women and National Socialism - Grossmann, Atina (Gender & History, 1991)
Keywords: 1900-1999; 1930-1939; 1940-1949; allemagne; cours; discipline; europe; fascisme; his4830; histoire; histoire des femmes*; histoire et politique; historiographie; holocauste; maternité; nazisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; seconde guerre mondiale; thématiques; violences; violences contre les femmes*; violences d'état; violences sexuelles

Homeplace : a site of resistance dans Yearning: race, gender, and cultural politics - Hooks, Bell (Yearning: race, gender, and cultural politics, 1990)
bell hooks crosses boundaries in major debates on postmodern theory, cultural criticism, and the politics of race and gender. She warns that “discourse” about “difference” is dangerously detachable from more essential struggles.
Keywords: 1900-1999; 1980-1989; afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; cours; discipline; féminisme afroaméricain; histoire et politique; patriarcat; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

Exotisme et altérité: Essai sur les fondements d'une critique de l'anthropologie - Affergan, Francis (Sociologie d'aujourd'hui, 1987)
Keywords: anthropologie; approches et analyses; cours; discipline; har4610; histoire et politique; premier cycle; racisme; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences

Women, violence and social control - Hanmer, Jalna; Maynard, Mary (Humanities, 1987)
Keywords: amériques; continuum de violences; cours; discipline; europe; royaume-uni; régions géographiques; sciences humaines; sociologie; thématiques; trs3500; violences; violences conjugales; violences contre les femmes*; états-unis

L'Arraisonnement des femmes : essais en anthropologie des sexes - Mathieu, Nicole-Claude (Editions de l'Ecole des hautes études en sciences sociales, 1985)
Arraisonner quelqu'un, c’est en vieux français tenter de le persuader, argumenter pour lui faire entendre raison. En termes de marine et de police sanitaire, arraisonner un navire, c'est l'interpeller, interrompre sa route pour le contrôler. Ainsi, c'est de la double face, matérielle et mentale, du contrôle et de la manipulation des femmes que traite ce livre collectif. Par l'analyse de sociétés très diverses, anciennes et modernes, comme par la critique des discours scientifiques, les auteurs — ethnologues, sociologues, linguistes – éclairent avec rigueur et imagination théoriques deux domaines encore peu explorés de la problématique des sexes : 1) L’élaboration sociale (politique) de la sexualité et la manipulation des mécanismes de la reproduction — dont l'exposé dément les explications naturalistes ; 2) Les conditions socio-sexuées de la connaissance, les effets sur la conscience de l’oppression matérielle subie et exercée — dont l'analyse exclut toute explication idéaliste. Si les deux sexes sont socialement construits, ce n'est pas de façon symétrique. Objets de raisonnements réducteurs et réduites dans leur corps et dans leur raison, soumises à persuasion ou raisonnées de force, inspectées, contrôlées dans leur tête et dans leur ventre tel un navire sa cargaison, son état sanitaire, son port d'attache : ainsi sont-elles créées « femmes » dans de multiples sociétés. Ainsi s'exerce l'arraisonnement des femmes.
Keywords: 1900-1999; anthropologie; approches et analyses; cours; discipline; domination masculine; europe; fem1000; france; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques; violences; violences contre les femmes*

Female sexual slavery - Barry, Kathleen (New York University Press, 1984)
Keywords: amériques; corps; cours; cycles supérieurs; discipline; fem1000; fem7000; fem9000; lit3220; premier cycle; prostitution; régions géographiques; sciences humaines; sociologie; thématiques; violences; états-unis

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

L'Envers de la nuit: les femmes contre la pornographie - Lederer, Laura; Audy, Monique; Dufresne, Martin (Collection Les Entêtées, 1983)
Keywords: 1900-1999; amériques; approches et analyses; corps; cours; discipline; droit; féminisme pop; premier cycle; psychologie; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

The death of nature: Women, ecology and the scientific revolution - Merchant, Carolyn (New York : Harper & Row, 1983)
Un examen de la révolution scientifique qui montre comment la vision mécaniste du monde de la science moderne a sanctionné l'exploitation de la nature, l'expansion commerciale sans retenue et un nouvel ordre socio-économique qui subordonne les femmes.
Keywords: approches et analyses; capitalisme; discipline; environnement; histoire; histoire des sciences; histoire et politique; incontournable; patriarcat; philosophie; progrès; projet charge mentale; santé; sciences humaines; systèmes d'oppressions; thématiques; violences; violences envers la nature; violences envers les femmes*; écoféminisme

Les enfants de Jocaste : l'empreinte de la mère - Olivier, Christiane (Médiations, 1980)
Voici "l'autre psychanalyse", la part féminine, celle que Freud n'a pas pu écrire. En face d'Oedipe, il y a Jocaste, sa mère, qui règne sur son fils en l'absence de Laïos, le père tué. Et Jocaste règne toujours, non seulement sur son fils, mais sur sa fille, en l'absence du père qui abandonne avec joie les soins et l'éducation du jeune enfant à sa femme. Soins et éducation qui sont ainsi monosexués alors que les enfants sont de deux sexes. Pour Christiane Olivier, femme et psychanalyste, c'est l'ombre de la mère, ressentie si différemment par le petit garçon et la petite fille, qui explique et nourrit l'antagonisme séculaire entre l'homme et la femme. Dans un style clair et accessible à tous, elle dresse le procès non pas de la maternité, mais du maternage, procès qui peut aussi se lire comme un mode d'emploi de la vie du couple. Elle démontre, avec humour, que la fameuse "envie du pénis" dont souffriraient les femmes pourrait bien n'être que la projection d'une "envie du sein" ou "envie de l'utérus" dont souffriraient les hommes, et que nos hommes politiques ayant parfois résolu leur Oedipe n'ont presque jamais résolu "leur Jocaste".
Keywords: cours; discipline; europe; fem1000; france; premier cycle; psychanalyse; régions géographiques; sciences; sciences humaines; thématiques; violences; écriture des femmes*

Pratique du pouvoir et idée de Nature (1) : l’appropriation des femmes - Guillaumin, Colette (Nouvelles Questions Féministes, 1978)
Dans les rapports de genre, le fait que les hommes puissent s'assurer la force de travail des femmes sans contrepartie mesurable (en temps, en argent, etc.) montre que la nature de la relation est différente de celle de la vente classique du travail. Comme dans l'esclavage et le servage, il y a appropriation directe de la base matérielle – corporelle – de l'individu. Cette appropriation se manifeste, dans la forme matrimoniale de cette relation, par le fait que le travail n'est pas évalué, par l'appropriation des produits – parmi lesquels les enfants –, par le droit illimité d'utiliser le corps de l'épouse. Elle s'exprime par la nature de certaines tâches : la responsabilité, par exemple, des besoins corporels du dominant et de ses dépendants. Ces tâches sont empiriquement associées à l'appropriation corporelle (du dominé), par exemple dans l'esclavage. La relation sociale que l'on pourrait appeler « sexage » est à la fois collective (appropriation collective des femmes par les hommes) et privée (comme dans le mariage, qu'il soit légal ou de droit commun).
Keywords: approches et analyses; care; discipline; domination masculine; féminisme matérialiste; patriarcat; rapports sociaux de sexe; ressource en ligne; sciences humaines; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; travail; violences

Violence et contrôle social des femmes - Hanmer, Jalna (Questions Féministes, 1977)
Keywords: 1900-1999; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem7000; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociologie; systèmes d'oppressions; thématiques; violences

The Destruction of American Indian families - Unger, Steven (Association on American Indian Affairs, 1977)
Responding to the need for a comprehensive source of information regarding the separation of American Indian children from their families, this book presents essays which: examine the Indian child-welfare crisis in contemporary, legal, and historical perspectives; document the human cost of the crisis to Indian parents, children, and communities; and report on innovative programs designed and implemented by the Indian tribes themselves. Specifically, this book includes the following sections and essay titles: (1) Contemporary Overviews ("The Destruction of American Indian Families" and "The Role of the Federal Government: A Congressional View"); (2) Historical Perspectives ("The Effects of Boarding Schools on Indian Family Life: 1928" and "'Kid Catching' on the Navajo Reservation: 1920"); (3) The Human Cost ("'The Drunken Indian': Myths and Realities"; "The Wasted Strengths of Indian Families", "The Human Cost of Removing Indian Children from Their Families", "Child-Welfare Services to Indian People in the Albuquerque Area", "Indian Child Welfare in Oregon", "The Ravage of Indian Families in Crisis", "The Question of Best Interest", and "The Placement of American Indian Children--The Need for Change"); (4) A Legal Perspective ("Parent and Child Relationships in Law and in Navajo Custom"); (5) Tribal Actions ("Indian Children and Tribal Group Homes: New Interpretations of the Whipper Man" and "Tribal Resolutions"). (JC)
Keywords: american indian families; amériques; approches et analyses; autochtones; cours; discipline; droit; famille; his4443; histoire et politique; premier cycle; racisme; racisme systémique; residential schools; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques; violence coloniale; violence systémique; violences; états-unis